2019
DOI: 10.1093/jrr/rry110
|View full text |Cite
|
Sign up to set email alerts
|

New real-time patient radiation dosimeter for use in radiofrequency catheter ablation

Abstract: In a previous study, we reported on a novel (prototype) real-time patient dosimeter with non-toxic phosphor sensors. In this study, we developed new types of sensors that were smaller than in the previous prototype, and clarified the clinical feasibility of our newly proposed dosimeter. Patient dose measurements obtained with the newly proposed real-time dosimeter were compared with measurements obtained using a calibrated radiophotoluminescence glass reference dosimeter (RPLD). The reference dosimeters were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 31 publications
0
21
0
1
Order By: Relevance
“…Although the wide acceptance of IVR procedures, such as PCI, has led to increasing numbers of interventions being performed, radiation exposures from IVR are conclusively higher, exposing both the IVR staff and the patient to high radiation doses. [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the wide acceptance of IVR procedures, such as PCI, has led to increasing numbers of interventions being performed, radiation exposures from IVR are conclusively higher, exposing both the IVR staff and the patient to high radiation doses. [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…2), which is a very simple and immediate reading dose measurement method without heating and annealing, compared to the conventional methods, such as thermoluminescent dosimeters 16 and radiophotoluminescence glass dosimeters 23 . This RTD comprised photoluminescence sensors (Y 2 O 2 S: Eu, Sm), an optical fiber cable, a photodiode, and a digital display that included the power supply, and can measure using a maximum of four sensors in one measurement 24–27 . The photoluminescence sensor size had a cylindrical shape with dimensions φ4.1 × 11.5 mm.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, which require the integration of novel modalities to reduce the maximum skin dose during radiation exposure (Dskin, max) [6,7]. Additionally, previous studies have demonstrated that an estimation of Dskin, max can be undertaken using various modalities including metaloxide-semiconductor field-effect transistors, four photoluminescence sensors attached to the back of the patients, and wireless dosimeter modalities [8][9][10][11]. Although this approach has been previously reported to have various benefits when estimating the real-time data of radiation exposure, subsequent evidence indicates that it had some limitations which restrict its benefits to specific institutions [12,13].…”
Section: Introductionmentioning
confidence: 99%